ICT Based Business Management Concept by East African Youth - Husaain, Musafi; Beluga, Isabella (oneamrd (One a Mllions Dreams Corporation), 2025)
The usage of information and communication technology among young people in the East African community varies, with some seeing it as a way to communicate with family and others seeing it as a diversion. Young people may use information and communication technology to start enterprises. Young professionals shouldn't just assume that they'll find employment elsewhere; instead, they should look into opportunities in small and medium-sized businesses. Young professionals in the East African community are unable to compete with one another because their perspective on conducting business via small and medium-sized enterprises is taken into consideration. The economies of these nations are at different levels, and they operate in different ways. The inspiration for this piece comes from the fact that the study examined young professionals in the East African community who are knowledgeable and communication technologies, and regrettably, they utilize them in a manner that does not allow small and medium-sized businesses that are successful. The primary objective of this research is to characterize information and communication technologies as an chance to purchase or sell products or services through medium- and small businesses. This study will offer a improved comprehension of the speaker, particularly among young professionals, to absorb knowledge and communicate it viewing technologies favorably as a chance to expand business through small and medium-sized businesses and to understand the method for marketing goods and controlling consumer behavior via their demands. young people in their careers by exchanging business ideas and forming connections with firms both domestically and abroad, one must acquire industry knowledge. knowledge transmitted through information and communication technology.